The Application of Anti-Abuse Provisions to Inheritance and Gift Tax Law using the Example of German Inheritance and Gift Tax - Linseis, Philippe (European Scientific Journal, ESJ, 2025)
Most tax systems have explicit or case-law-based anti-abuse provisions. In Germany, such a regulation was legally standardized in § 42 AO. In the past, literature and case law in this context have mostly dealt with cases from income tax law. However, as will be shown below, anti-abuse legislation also plays an important role in inheritance and gift tax law. Special features arise here, above all, from the different taxation depending on the degree of kinship, which is not known in the income tax law and benefits for business assets in § 13a ErbStG. The aim of the article is to investigate the application of the general anti-abuse provision to inheritance tax law by analyzing legal literature and case law. Findings show that there is only very little literature or case law that explicitly deals with the topic. Nevertheless, as result, it can be stated that general anti-abuse provisions are, without limitation, applicable to inheritance and gift tax law and have high practical relevance.